UPAYA PENINGKATANKETERAMPILAN MEMBACA MELALUI PENGGUNAAN MEDIA PIAS-PIAS KATA PADA SISWA KELAS 1A SEMESTER II SD NEGERI BANDUNGREJO 1 TAHUN PELAJARAN 2013/2014 - A. Zulaekah (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2014)
From the results of preliminary observations made to the State 1ASD grade students Bandungrejo 1 Karanganyar District of Demak, the author feels there are still shortcomings in learning Indonesian with the subject matter of reading the short text lancer. Deficiencies in learning Indonesian is because teachers have not been using the medium of learning interesting and challenging student activity. This study uses a Class Action Research (PTK). The design of this research action research (Action Research) by using the spiral model. The stages in the implementation of this research is conducted through two cycles. In the classroom action research was used the analysis of quantitative data such as cognitive learning outcomes assessment. The average value before the improvement of learning is then increased to 74.80 66.67 to 80.40 in the first cycle and the second cycle. Percentage of completeness students also increased, where before it was held instructional improvement, the percentage of completeness only 67.00% then increased to 85.00% in the first cycle and 100% in cycle instructional media II. Improve students' ability to read fluently some simple sentences consisting of 3-5 words with proper intonation. Keywords: PTK, reading, Media Pias-Pias